Native and ornamental exotic resources in pollen loads and garbage pellets of four stingless bees (Apidae, Meliponini) in an urban environment with riparian native forest - Vossler, Favio Gerardo (2019)
An entomopalynological study to assess pollen use by wild bees was performed in an urban environment with riparian native forest in the Chaco region of Argentina. A combined method for sampling pollen loads and garbage pellets at nest entrances in four stingless bees with different entrance size and forager traffic was here successfully used. Sampling was carried out in a short period of time (late winter) and located within a distance of 50 m. Pollen analysis using acetolysis showed that most identified pollen types (31) were from native species, 12 from ornamental exotic species, 5 included native and ornamental exotic species and 18 of uncertain status. A much broader pollen spectrum was present in garbage pellets (62 types) than loads (14 types). A few resources from previous blooming (late spring-summer) were identified in garbage pellets, which were mainly composed of current flowerings. From the 66 pollen types found in all samples, many (18) remained unidentified due to the complex nature of the vegetation surrounding the nests and the generalist behaviour of these bees. The versatile foraging behaviour on spontaneous (mostly native) and cultivated (mostly ornamental exotic) pollen resources is an important issue for the conservation and rearing of stingless bee colonies in urban habitats where native flora is preserved, particularly the riparians, where a high richness of blooming plants is available.